The Struggle for the Streets of Berlin Politics, Consumption, and Urban Space, 1914-1945 - Loberg, Molly Jean 1976- (Cambridge University Press, 2018)
Contests over Berlin's streets in the interwar period reveal the fragility of consumer capitalism, urban order, and liberal democracy.